Employee Engagement dan Kepuasan Kerja Dampaknya Terhadap Kinerja Karyawan - Meliuspendi, Kadek; Gede Sadiartha, A.A.Ngurah; Putri Trarintya, Mirah Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of employee engagement and job satisfaction on employee performance. This research was conducted at PT. Paramitha Auto Graha which is located at Jalan A. Yani No. 999 Peguyangan Denpasar, Bali. This research was conducted on 36 employees using the census method. Interview and observation methods at the pre-survey stage followed by distributing questionnaires to respondents were used to collect data. The results of the respondents' answers were then tested for validity and reliability using SPSS software, followed by classical assumption tests and multiple linear regression analysis. The results of the study prove that employee engagement and job satisfaction partially have a positive and significant effect on employee performance.